Is fiscal policy one of the most important socio-economic drivers for entrepreneurial activity in European Union countries? - Oana-Ramona Lobonț; Florin Costea; Sorana Vătavu; Zheng-Zheng Li; Alexandra-Mădălina Țăran; Igor Kononenko (Journal of Business Economics and Management (JBEM), 2023)
This research highlights the extent to which fiscal policies, along with government effectiveness, trade, economic growth, and education, influence the entrepreneurial environment, starting from the assumption that the effectiveness of public policies and the public administration support for entrepreneurship has proven to be a trigger for development and a means of reducing social inequalities and increasing well-being. Our analysis is based on a panel threshold regression model, which returns parameters for the predictors, in which there is a changing point in fiscal policy as the threshold variable on entrepreneurship activity. The database consisted of annual data from 2002-2019, referring to the European Union's member states, presented visually based on the data mapping process to evidence the hierarchy of the EU countries for each of the analysed phenomena. Our results evidenced tax policy, trade, and government effectiveness as significant influential factors in stimulating entrepreneurship in EU countries. Although GDP growth and education positively influenced entrepreneurial activity, the statistical tests did not confirm it. Therefore, Governments can encourage entrepreneurial opportunities through harmonised tax legislation with EU regulations and a lighter regulatory burden and policies that foster competition, lower taxes, increase transparency and provide open access for all businesses.
Keywords: H21; H32; C24; 650; dynamic panel threshold model; education; entrepreneurship; European Union; fiscal policy; governance